THE EFFECT OF BANANA CORM MANURE TO THE GROWTH AND YIELD OF CELERY IN PEAT SOIL - ridha, muhammad; Wasi'an, Wasi'an; Budi, Setia (Jurnal Sains Pertanian Equator, 2019)
ABSTRACT This study aims to determine the best concentration of banana corm manure to the growth and yield of celery plants on peat soil. This research was conducted in the experimental garden of Faculty of Agriculture, Tanjungpura University, Pontianak. The study took place from 05 February 2018 to 12 April 2018. The design of this study used a field experimental method with Completely Randomized Design (CRD) consisting of 5 treatments with 5 replications, each experimental unit consisting of 3 sample plants. The treatments were arranged in a series of manure concentration, a1 = without addition of banana corm manure , a2 = concentration of banana corm manure 10% equals to 100 ml/liter, a3 = concentration of banana corm manure 20% equals to 200 ml/liter, a4 = concentration of banana corm manure 30% equals to 300 ml/liter and a5 = concentration of banana corm manure 40% equals to 400 ml/liter. The variables observed in this study were root volume, leaf chlorophyll, number of petiole, dry weight of plant and fresh weight of plant. The researh showed that the provision of liquid manure with 10% banana corm manure equivalent to 100 ml/liter is an efficient concentration that can increase the growth and yield of celery on peat soil. Keywords: Banana corm manure, Celery, Peat soil